Study on the influencing factors and strategies of sorted collection of urban refuse in China (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Although the sorted collection of urban refuse in China started later than that in developed countries, it has been sustained 14 years since the implementation of pilot project of waste sorting. However, the waste sorting among cities is still making slow progress and beset with difficulties in China. With a review of the actual situation of waste sorting in China, this article firstly introduced the urban refuse sorted way in China, and then analysed the influencing factors of the sorted collection of urban refuse. At last, we put forward some strategies and suggestions for dealing with the prominent challenges of the sorted collection of urban refuse in China.